Collaborative impact of the NAO and atmospheric blocking on European heatwaves, with a focus on the hot summer of 2018. (14th October 2020) - Li, Muyuan; Yao, Yao; Simmonds, Ian; Luo, Dehai; Zhong, Linhao; Chen, Xiaodan
Abstract: Two intense heatwaves of July and early August 2018 are found to be associated with a European blocking (EB) event accompanied by a series of consecutive positive North Atlantic Oscillation (NAO + ) events. Further analyses show that the collaborative role of an EB event and its upstream NAO + pattern could increase the frequency, persistence, magnitude and scale of heatwaves over Europe. Compared with NAO + -unrelated EB events, NAO + -related EB events are less movable (quasi-stationary) and more persistent over Europe, which could contribute to an increase in the intensity and persistence of heatwaves. In addition, the blocking high of this type has a northeast–southwest orientation with stronger warm airflow and less precipitation in northern and western Europe, where large scopes of higher temperatures tend to occur. In contrast, NAO + -unrelated EB events without orientation correspond to a trough in the south, which results in increased precipitation and cold air in the southern part of Europe, and thus high temperatures contract to the northern part of Europe. Moreover, considering that the NAO + pattern leads the formation of an EB event, the NAO + pattern might serve as a potential predictor for European heatwaves. Our conclusions are strongly supported by the analysis of CMIP6 historical simulations which also capture the differences of high temperatures and atmospheric circulations between NAO + -related EB events and NAO + -unrelated EB events.